2011
DOI: 10.3109/10673229.2011.549769
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Implications of Music: Insight from Neuroscientific and Clinical Studies

Abstract: Neuroscientific and clinical studies of music over the past two decades have substantially increased our understanding of its use as a means of therapy. The authors briefly review current literature related to music's effect on people with different mental illnesses, and examine several neurobiological theories that may explain its effectiveness or lack thereof in treating psychiatric disorders. Neuroscientific studies have shown music to be an agent capable of influencing complex neurobiological processes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 82 publications
0
68
0
3
Order By: Relevance
“…In recent years, music has been advocated as a therapeutic method to manage patients' pain and anxiety. 5 The study by Lin and associates 6 had confirmed that patients' spiritual, emotional, and psychological feelings could be satisfied by music intervention, and music engagement became more and more popular in perioperative care as an adjuvant therapy. 7 To our knowledge, there has been no research on reducing paitents' discomfort and anxiety during flexible cystoscopy by music intervention.…”
mentioning
confidence: 99%
“…In recent years, music has been advocated as a therapeutic method to manage patients' pain and anxiety. 5 The study by Lin and associates 6 had confirmed that patients' spiritual, emotional, and psychological feelings could be satisfied by music intervention, and music engagement became more and more popular in perioperative care as an adjuvant therapy. 7 To our knowledge, there has been no research on reducing paitents' discomfort and anxiety during flexible cystoscopy by music intervention.…”
mentioning
confidence: 99%
“…[10]. It is also applicable to people with schizophrenia, who are suffering from insomnia; listening to music before going to bed improved patients' sleeping qualities [11].…”
Section: Passive Music Therapymentioning
confidence: 99%
“…L'écoute musicale permettrait une amélioration à court terme de l'humeur, plus grande que celle obtenue via le seul usage du traitement standard de la dépression. La musique aurait donc des effets psychophysiologiques positifs chez les patients déprimés (Lin et al, 2011). L'activité électroencéphalographique (Field et al, 1998), la séroto-nine (Evers et Suhr, 2000) et le facteur neurotrophique dérivé du cerveau (BDNF) dans l'hippocampe (Chikahisa et al, 2006 ;Angelucci et al, 2007), pourraient être impliqués dans les mécanismes biologiques soustendant l'effet thérapeutique de l'écoute musicale dans la dépression.…”
Section: Les Caractéristiques Individuellesunclassified